Protein binding determination of DHA in human plasma by HPLC using post-column on-line alkali derivatization and UV detection - Zhang, Xiaonan (My University, 2010)
Artemisinin and its derivatives are considered as a very important new class of antimalarials and becoming more and more commonly used throughout the world. Dihydroartemisinin (DHA) is the main bioactive metabolite of artemisinin in clinical use and has greater intrinsic atimalarial activity. Although pharmacokinetic research in vivo and in vitro has been done and conventional pharacokinetic parameters for DHA are well documented, data relating to parameter of protein binding of DHA is still inconsistent. In this project, equilibrium dialysis and ultrafiltration methods were carried out to determine the protein binding percentage of DHA in healthy human plasma. At the same time, HPLC conditions for DHA quantification wer optimized during experiments. Protein binding fraction of DHA was reported here as 80%-84% considering the volume shifts in equilibrium dialysis and 88%-91% in various DHA concentrations in ultrafiltration
Keywords: Industriell bioteknik; Industrial Biotechnology